Neurosciences and the christian antropology: an introduction - Fischer, Gerson Joni (Vox Scripturae - Revista Teológica Internacional, 2015)
This present introduction has Neurosciences and Christian Anthropology as its central theme. The approximation takes place through its philosophical bias for theological considerations to be made subsequently. Within scientific environments, the belief in the existence of a Self that is master over one’s body is being considered as an infirmity. This belief raises the inquiry of whether it is possible, based on existing knowledge of brain function, to assume the human being as a bimolecular machine that reacts solely to the law of causality. Is there no longer room to expatiate about the soul? Does an explanation of a strictly biological order on the event of consciousness contribute to defending of the value of humankind? These discussions guarantee involvement of Christians with the theme, for the Self is the central subject of the love of God, according to biblical testimony. The current phase of the debate suggests that arrangements of Cartesian Dualism and reductionist monism are not presented as alternatives to answer these and other inquiries. Personal liberty and conscience are, by far, fully deciphered enigmas. It is the person, not a part of her, who understands, thinks, remembers, becomes emotional, motivates herself, is alert and produces impulses. Men and women, according to biblical testimony, are integral and indivisible living creatures, fallen in sin, expelled from the presence of God, and in need of reconciliation. The structural and materialistic variable of the old Cartesians is equivalent to the assertion that a body exists, and that it is in its brain. Therefore, it is necessary to overcome this idea that there is something in mind, which makes it conscious. The daily lives of people bring to light that they simply are all of this that is presented in an indivisible manner. The Cartesian soul theory, which aims to produce a thinking being, seems no longer necessary. Knowledge on the workings of neurons convert the small gray organ into something sufficient to make a conscious life emerge. Reasoning together, can the soul be rejected once it is assimilated as the manifestation of life itself? It is imminent to ensure the tension implied in the affirmation of the body and the life manifested in it. The dialog has an interdisciplinary character. It should therefore, serve both the development of the most refined discoveries on brain anatomy and physiology and their ethical use, and the affirmation of human value, which transcends them. The Evangelical incumbency is to announce the conquest over all dualisms, which is the reconciliation of man in Christ.